2015
DOI: 10.1093/ejo/cju101
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular advancement appliances for the treatment of paediatric obstructive sleep apnea: a systematic review

Abstract: The current limited evidence may be suggestive that MAAs result in short-term improvements in AHI scores, but it is not possible to conclude that MMAs are effective to treat pediatric OSA. Medium- and long-term assessments are still required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 82 publications
1
53
0
4
Order By: Relevance
“…& Mandibular advancement appliances improve AHI and nadir oxygen saturation, but long-term efficacy has not been established [32,33]. & Maxillomandibular advancement, while rarely performed in children, is a surgical option for adolescents with severe OSA and craniofacial anomalies such as micrognathia [34].…”
Section: Orthodontic Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…& Mandibular advancement appliances improve AHI and nadir oxygen saturation, but long-term efficacy has not been established [32,33]. & Maxillomandibular advancement, while rarely performed in children, is a surgical option for adolescents with severe OSA and craniofacial anomalies such as micrognathia [34].…”
Section: Orthodontic Treatmentmentioning
confidence: 99%
“…Mandibular advancement appliances (MAA) can increase the lateral dimension of the velopharyngeal airway as a result of forward positioning of the mandible and also reduce collapsibility of the airway. A recent systematic review of MMA use in children with OSA demonstrated improvements in AHI but failure to normalize PSG parameters [32]. The studies regarding MMA feature small sample sizes and lack of control groups.…”
Section: Mandibular Advancement Appliancesmentioning
confidence: 99%
“…Thirteen reviews were on adult OSA (2 SRs and 11 SRs with MAs), 1,[49][50][51][52][53][54][55][56][57][58][59][60] and four reviews were on pediatric OSA (3 SRs and 1 SR with MA). 12,15,61,62 Key methodological and descriptive characteristics of the included reviews are presented in Tables 2 and 3.…”
Section: R Esu Lt Smentioning
confidence: 99%
“…With respect to the pediatric OSA reviews, the comparison groups included no treatment, placebo, and pretreatment and posttreatment with only one OA type. Two reviews 12,62 included studies on maxillary expansion with and without concurrent use of fixed orthodontic appliances. Another review 15 included five RCTs that assessed seven independent interventions with only one of those targeting OAs.…”
Section: R Esu Lt Smentioning
confidence: 99%
See 1 more Smart Citation